2012
DOI: 10.4081/pmc.2012.64
|View full text |Cite
|
Sign up to set email alerts
|

Videogame playing as distraction technique in course of venipuncture

Abstract: Riassuntole procedure di venipuntura ed incannulamento venoso sono la causa più comune di dolore e distress nel bambino. ridurre il dolore e l'ansia ad esse correlati potrebbe essere importante per prevenire le reazioni di distress in corso di ulteriori procedure, soprattutto per quei bambini con patologia cronica che necessitano di controlli o ricoveri multipli. l'obiettivo di questo trial randomizzato controllato, condotto in aperto, è stato quello di valutare nel bambino l'efficacia dell'aggiunta di una str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
2
9
0
2
Order By: Relevance
“…MacLaren et al (23) showed that playing a video game was less effective in providing pain relief than watching television. Another study showed that playing video games did not lead to any improvements in analgesia during venipuncture in children treated with local anaesthetic (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MacLaren et al (23) showed that playing a video game was less effective in providing pain relief than watching television. Another study showed that playing video games did not lead to any improvements in analgesia during venipuncture in children treated with local anaesthetic (9).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the actual distraction techniques, there is an increasing interest in the use of new technology, such as electronic games and virtual reality (8)(9)(10).…”
Section: Key Notesmentioning
confidence: 99%
“…Other techniques of analgesia, such as light sedation, are standard of care in many institutions and include medications such as midazolam or inhaled nitrous oxide and non-pharmacological interventions [79]. Cochrane meta-analysis has demonstrated that certain non-pharmacological interventions help manage or reduce needle related pain [1012], but we found no studies regarding the efficacy of non-pharmacological treatments for recurrent needle procedures.…”
Section: Introductionmentioning
confidence: 91%
“…where the child is presented with music or a video during the procedure with successful results; or active distractions, e.g. asking the child to play an interactive game [34] or more physical tasks such as blowing soap bubbles [44]. Breathing tasks have gained attention because the activity itself could calm the child and stabilize the quick shallow breathing often associated with anxiety.…”
Section: Introductionmentioning
confidence: 99%